CIC inactivating mutations identify aggressive subset of 1p19q codeleted gliomas. Issue 3 (27th July 2015) - Gleize, Vincent; Alentorn, Agusti; Connen de Kérillis, Léa; Labussière, Marianne; Nadaradjane, Aravidan A; Mundwiller, Emeline; Ottolenghi, Chris; Mangesius, Stephanie; Rahimian, Amithys; Ducray, François; on behalf of the POLA network; Mokhtari, Karima; et al.
<x xml:space="preserve">Abstract</x> Objective CIC gene is frequently mutated in oligodendroglial tumors with 1p19q codeletion. However, clinical and biological impact remain poorly understood. Methods We sequenced the CIC gene on 127 oligodendroglial tumors (109 with the 1p19q codeletion) and analyzed patients' outcome. We compared magnetic resonance imaging, transcriptomic profile, and CIC protein expression of CIC wild‐type (WT) and mutant gliomas. We compared the level of expression of CIC target genes on Hs683‐IDH1R132H cells transfected with lentivirus encoding mutant and WT CIC. Results We found 63 mutations affecting 60 of 127 patients, virtually all 1p19q codeleted and IDH mutated (59 of 60). In the 1p19q codeleted gliomas, CIC mutations were associated with a poorer outcome by uni‐ (p = 0.001) and multivariate analysis (p < 0.016). CIC mutation prognostic impact was validated on the TCGA cohort. CIC mutant grade II codeleted gliomas spontaneously grew faster than WTs. Transcriptomic analysis revealed an enrichment of proliferative pathways and oligodendrocyte precursor cell gene expression profile in CIC mutant gliomas, with upregulation of normally CIC repressed genes ETV1, ETV4, ETV5, and CCND1. Various missense mutations resulted in CIC protein expression loss. Moreover, a truncating CIC mutation resulted in a defect of nuclear targeting of CIC protein to the nucleus in a human glioma cell line expressing IDH1R132H and overexpression of CCND1 and other new target genes of CIC, such as DUSP4 and SPRED1. Interpretation CIC mutations result in protein inactivation with upregulation of CIC target genes, activation of proliferative pathways, inhibition of differentiation, and poorer outcome in patients with a 1p19q codeleted glioma. Ann Neurol 2015;78:355–374